2020
DOI: 10.1177/2045894020950186
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical utilization of risk assessment tools in pulmonary arterial hypertension: a descriptive survey of facilitation strategies, patterns, and barriers to use in the United States

Abstract: Practice guidelines suggest that treatment decisions in pulmonary arterial hypertension be informed by periodic assessment of patients’ clinical risk. Several tools, well validated for risk discrimination, such as the Registry to Evaluate Early and Long-term Pulmonary Arterial Hypertension Disease Management calculator, were developed to assess pulmonary arterial hypertension patients’ risk of death based on multiple parameters, including functional class, hemodynamics, biomarkers, comorbidities, and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…However, at the same time, many also expressed that their QoL might improve with parenteral prostacyclin therapy by reducing symptoms and slowing disease progression. In fact, most of the patients in Group B: Refused/Initiated indicated that their QoL improved upon initiating therapy, which is consistent with studies that evaluated QoL following initiation of parenteral prostacyclin therapy (16)(17). Moreover, these patients indicated that their initial concerns of the pump affecting their QoL were mostly unwarranted.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, at the same time, many also expressed that their QoL might improve with parenteral prostacyclin therapy by reducing symptoms and slowing disease progression. In fact, most of the patients in Group B: Refused/Initiated indicated that their QoL improved upon initiating therapy, which is consistent with studies that evaluated QoL following initiation of parenteral prostacyclin therapy (16)(17). Moreover, these patients indicated that their initial concerns of the pump affecting their QoL were mostly unwarranted.…”
Section: Discussionsupporting
confidence: 80%
“…The use of newly developed risk assessment tools could aid in the identification of highrisk patients and objectively communicate that risk to the patient 17 . In addition to the objective assessment of disease severity, clinicians should consider addressing patient perceptions of parenteral prostacyclin therapy's negative impact on QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key barriers included uncertainty around when and how to apply the CSRS recommendations, lack of resources (e.g., cardiac monitors), lack of buy-in from the broader medical team, discomfort (hesitancy) using CSRS, and lack of evidence about the impact on patient outcomes. Surprisingly, no reference on workload or time constraint was brought up, as is often found in other studies (39)(40)(41)(42). Our ndings suggest that physician capability should be a central target of implementation supports, speci cally the capability to interpret CSRSbased criteria and apply it across a range of clinical presentations.…”
Section: Discussionmentioning
confidence: 63%
“…In our study, participants largely referred to educational meetings (e.g., combined grand rounds inclusive of all relevant specialities) and educational videos. Skill-building can be supplemented by creating increased opportunity to utilize the CSRS, including integration into the EMR, engaging local champions, displaying posters, and sending e-mail communications to encourage use (41,42,46). This suite of strategies are commonly used in the ED setting (46) and have demonstrated effectiveness in promoting guideline-adherent care (47).…”
Section: Discussionmentioning
confidence: 99%